The Longitudinal Parallel Process Analysis of Biomarkers of Oxidative Stress, Symptom Clusters, and Cognitive Function in Children With Leukemia. (July 2020) - Hooke, Mary C.; Hatch, Daniel; Hockenberry, Marilyn J.; Whitman, Susan; Moore, Ida; Montgomery, David; Marano, Kari; Mitby, Pauline; Scheurer, Michael E.; Taylor, Olga; Pan, Wei
Background: During treatment for acute lymphoblastic leukemia (ALL), children report co-occurring symptoms of fatigue, sleep disturbance, pain, nausea, and depression as a symptom cluster. Central nervous system–directed ALL therapies also put children at risk for cognitive impairments. Cancer therapies can cause an increase in oxidative stress, which may contribute to treatment-related symptoms. This study examined the longitudinal relationships between biomarkers of oxidative stress in the cerebrospinal fluid, the Childhood Cancer Symptom Cluster–Leukemia (CCSC-L), and cognition, in children over the first year of ALL treatment.Methods: Glutathione (GSH) biomarkers of oxidative stress were measured in cerebrospinal fluid collected during treatment lumbar punctures. GSH biomarkers, symptoms, and cognitive function of 132 children aged 3 to 18 years were evaluated at four time points during the first year of leukemia treatment. Participants, 7 years and older, completed self-report measures, and parents reported for younger children. Cognitive function measurements for all participants were completed by parents. A longitudinal parallel-process model was used to explore the influence of the initial measurement and the subsequent change over four time points of the GSH biomarkers on the CCSC-L and cognition.Results: GSH biomarkers increased over the four time points indicating decreasing oxidative stress. When GSH biomarkers were higher (less oxidative stress) at the initial measurement, the CCSC-L severity was lower, cognition was better, and cognition improved over the four measurements. Screening children for high levels of oxidative stress would be a foundation for future intervention studies to address symptom distress and cognitive impairments.